SCHIZOPHRENIA IN ADAM PETRAZELLI AS THE MAIN CHARACTER OF WORD ON BATHROOM WALLS FILM - Salwa, Salsabila Safira; Budiwaty, Suci (UG Journal, 2021)
Schizophrenia is chronic psychiatric disorder when the sufferers experienced hallucinations, delusions, confusion in thinking, and attitude change. People with Schizophrenia generally experienced symptoms of psychosis, namely the difficulty of distinguishing between realities with the mind that is on itself. The aims of this research were to find out the Schizophrenia symptoms that were suffered by Adam Petrazelli, as the main character in Words on Bathroom Walls film by using Nevid Jeffery’s theory and to find out the type of Schizophrenia that was suffered by Adam Petrazelli based on Halonen and Santrock’s theory. This research used qualitative method. The writers found that there were 5 symptoms of Schizophrenia that were suffered by Adam Petrazelli, there were four hallucination, eight delusion, one thought and speech disorder, one disturbance of emotional, and one inability to sustain attention. While the type of Schizophrenia that was suffered by Adam was Paranoid Schizophrenia.